European constitution of corporations : legal personhood, legal powers & legal governance of corporate entities in the European Union - Raskulla, Siina (Tampere University dissertations, ISSN 2490-0028, 2022)
Abstract.
Keywords: Euroopan unioni; yritykset; yritykset : EU-maat; yhtiöt; EU-oikeus : yhtiöoikeus; finanssikriisi; taloudelliset kriisit; yhteiskuntavastuu; Hohfledin revisioitu typologia